Total Body Skin Examination Practices: A Survey Study Amongst Dermatologists at High-Risk Skin Cancer Clinics - Shirin Bajaj; Zachary J. Wolner; Stephen W. Dusza; Ralph P. Braun; Ashfaq A. Marghoob; Jennifer DeFazio (Mattioli1885, 2019)
Background/Objectives: Although total body skin examination (TBSE) is the primary screening mechanism for melanoma, there is no consensus on which anatomic sites a screening TBSE should include. We sought to establish which anatomic sites are examined during routine (>90%) TBSEs of patients at high risk for skin cancer. Methods: A Google survey was emailed to 173 international dermatologist skin cancer specialists. Results: More than 75% of participants reported routinely examining the scalp, ears, face and neck, trunk, breasts, inframammary areas, axillae, extremities, palms and soles, nails, interdigital spaces, and buttocks. The least frequently inspected anatomic sites included genitalia, with male genitalia more frequently examined than female (penis n = 39; 52%; labia majora n = 21; 28%; P = 0.003), the perianal region (n = 26; 34.7%), and the ocular conjunctiva and oral mucosa (n = 35; 46.7%). Participants cited not screening these areas because of perceived patient discomfort, low prevalence of malignancy, and the expectation that other specialists examine the area. Conclusions: The role of routine surveillance of neglected anatomic sites is unclear and warrants further discussion weighing potential mortality benefit against the incidence of melanoma in obscure sites, morbidity of intervention in sensitive sites, cost-effectiveness, and potential for patient discomfort.